AGRARIAN RECEIPTS OF AGRICULTURAL ENTERPRISES IN ACTIVATION OF THE COUNTRY'S FOOD SUPPLY - Levandivskyi, O. T.; Svynous , N. I.; Krykhovetska , Z. M. (The actual problems of regional economy development, 2024)
The problem of attracting additional resources to the agricultural sector is an important task for agricultural enterprises, whose activities are of great importance for the food supply of the State. The article examines the arguments and counter-arguments for using agrarian receipts as an investment instrument for agricultural producers. The main purpose of the study was to analyse the current state of use of agrarian receipts in the activities of agricultural enterprises, to identify advantages and disadvantages, and to determine the prerequisites and prospects for increasing the volume of these instruments. The article analyses their essence and studies the positive impact of agrarian receipts on domestic agriculture. The use of agrarian receipts allows adapting the attracted funds to the needs of agricultural enterprises. The study of these documents of title has revealed that they are certain types of documents used in the sphere of economic activity to mediate certain actions with property and property rights. The article analyses the dynamics of their use in the period from 2015 to 2023. The article also considers the use of agrarian receipts in the regions of Ukraine, in particular, where the pilot project was implemented. The article suggests ways to increase the use of agrarian receipts throughout Ukraine. The article also explores the problems of developing lending to agricultural enterprises through agricultural receipts. The results of the analysis show that this practice is effectively applied in the activities of agricultural enterprises in Ukraine. The article analyses the volumes of bank lending to agriculture and establishes that the volumes of agrarian receipts almost equal the volumes of bank lending to the agricultural sector for a short period in the national currency, which contributed to a significant expansion of working capital financing in the agricultural sector. The article identifies further directions for the development of the use of agrarian receipts, in particular, with the participation of bank lending secured by a financial agrarian receipt. The main issues that need to be addressed to create conditions for refinancing and securitisation of agricultural receipts are outlined.